Fotobiološka varnost nekaterih virov nekoherentnih umetnih optičnih sevanj - Klanjšek Gunde, Marta (Vakuumist, 2010)
Photobiological safety of three non-coherent optical radiation sources was analysed according to the new Regulation on the protection of workers from risks related to exposure to artificial optical radiation sources. Three sources were analysed, laboratory VV-curing equipment, UV-A radiation source and xenon lamp. Spectral irradiances were measured on positions where a personis likely to be present when working with particular equipment. Exposure levels for skin and eyes were calculated for ultraviolet and visible radiation. The protection ability of the lab coat textile, protective goggles and gloves were analysed. The blue light hazard was found to be negligible for all three radiation sources without any protection. However, a person with unprotected skin and eyes is allowed to be exposed to ultraviolet radiation for up to some minutes, depending on radiation source and its application. Hazardous effects of ultraviolet radiation are greatly diminished by protective cloth, gloves and goggles. Rather poor protection is achieved by textile and better by gloves and goggles.
Keywords: fotobiološka zaščita; security; škodljivost; tveganje; UV sevanje; varnost